Suppression of LPS-induced matrix-metalloproteinase responses in macrophages exposed to phenytoin and its metabolite, 5-(p-hydroxyphenyl-), 5-phenylhydantoin - Serra Ryan; Al-saidi; Angelov Nikola; Nares Salvador (BMC, 2010)
Abstract Background Phenytoin (PHT) has been reported to induce gingival (gum) overgrowth (GO) in approximately 50% of patients taking this medication. While most studies have focused on the effects of PHT on the fibroblast in the pathophysiology underlying GO, few studies have investigated the potential regulatory role of macrophages in extracellular matrix (ECM) turnover and secretion of proinflammatory mediators. The aim of this study was to evaluate the effects of PHT and its metabolite, 5-(p-hydroxyphenyl-), 5-phenylhydantoin (HPPH) on LPS-elicited MMP, TIMP, TNF-α and IL-6 levels in macrophages. Methods Human primary monocyte-derived macrophages (n = 6 independent donors) were pretreated with 15-50 μg/mL PHT-Na+ or 15-50 μg/mL HPPH for 1 hour. Cells were then challenged with 100 ng/ml purified LPS from the periodontal pathogen, Aggregatibacter actinomycetemcomitans. Supernatants were collected after 24 hours and levels of MMP-1, MMP-2, MMP-3, MMP-9, MMP-12, TIMP-1, TIMP-2, TIMP-3, TIMP-4, TNF-α and IL-6 determined by multiplex analysis or enzyme-linked immunoadsorbent assay. Results A dose-dependent inhibition of MMP-1, MMP-3, MMP-9, TIMP-1 but not MMP-2 was noted in culture supernatants pretreated with PHT or HPPH prior to LPS challenge. MMP-12, TIMP-2, TIMP-3 and TIMP-2 were not detected in culture supernatants. High concentrations of PHT but not HPPH, blunted LPS-induced TNF-α production although neither significantly affected IL-6 levels. Conclusion The ability of macrophages to mediate turnover of ECM via the production of metalloproteinases is compromised not only by PHT, but its metabolite, HPPH in a dose-dependent fashion. Further, the preferential dysregulation of macrophage-derived TNF-α but not IL-6 in response to bacterial challenge may provide an inflammatory environment facilitating collagen accumulation without the counteracting production of MMPs.